Performance evaluation of a new time of flight PET/CT scanner: Results of a multicenter study. (December 2019) - Zorz, Alessandra; Matheoud, Roberta; Richetta, Elisa; Baichoo, Saraswati; Poli, Matteo; Scaggion, Alessandro; Pellerito, Riccardo Emanuele; Cuppari, Lea; Sacchetti, Gian Mauro; Stasi, Michele; Paiusco, Marta; Brambilla, Marco
Highlights: NEMA NU-2 2012 performance of the new Ingenuity TF PET/CT were in agreement for the three scanners included in this study. NEMA results were in agreement with the values declared by the manufacturer. Based on image quality phantom, PSF correction was the parameter that impacted mainly on the contrast recovery coefficient. Contrast recovery coefficient does not depend on iterations and amplitude of Gaussian filter. Abstract: Purpose: The aim of this multicenter study was to evaluate the performance of the upgraded version of the Ingenuity TF PET/CT scanner, according to the NEMA NU-2 2012 standards. Methods: Spatial resolution, sensitivity, count rate response, scatter fraction, image quality and accuracy were evaluated on three Ingenuity TF scanners installed in Italian hospitals. Furthermore, energy and timing resolution were measured. A detailed image quality phantom analysis was performed to evaluate the effect of different clinical reconstruction parameters, including the application of PSF correction. Results: Results show an average spatial resolution of 4.7 mm and an average absolute system sensitivity of 7.9 cps/kBq. The average maximum NECR was 119.83 kcps at 20.67 kBq/ml, while the maximum true event rate was 322.62 kcps at the concentration of 24.51 kBq/ml. The average maximum bias below NECR peak was 12.58%. All the results of NEMA tests were in agreement with the values declared by the manufacturer. The estimated average energy and timing resolution were 10.83% and 536.2 ps, respectively. Image quality phantom analysis obtained with different reconstruction settings showed that PSF correction was the parameter that affected mainly on contrast recovery coefficient, while the iteration number and amplitude of Gaussian filter had no significant effect. Of relevance, the application of PSF correction never led to recovery coefficient values higher than 100% and to Gibbs or edge artifacts. Conclusions: The new Ingenuity TF model shows physical performance similar to other scanners of the latest generation for all standard NEMA NU2-2012 measurements.